The Role of Visual Elements in Understanding News Videotext: the Case of Syrian EFL Learners at the Intermediate Level - ديما ديوب (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study explores how Syrian EFL students at the intermediate level comprehend news videotext. It particularly focuses on the role of visuals in comprehension. To this end, three groups totaling 41 students of English as a Foreign Language at the Higher Institute of Languages viewed BBC news clips during three 45-minute sessions. News videotexts were repeatedly paused, and participants were invited to write down immediately retrospective individual reports on what elements of the news videotext helped or hindered comprehension. Data analysis was enriched by principles of multimedia learning. Overall, the mediating role of the visual elements in comprehension was manifest in the data. Evident too was the interplay between audio and visual processing of news content, which underlines the need for strengthening learners’ media literacy as part and parcel of news videotext comprehension.